2020
DOI: 10.1007/s10143-020-01298-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of hypothalamic hamartomas

Abstract: Hypothalamic hamartomas are aberrant masses, composed of abnormally distributed neurons and glia. Along endocrine and cognitive symptoms, they may cause epileptic seizures, including the specific gelastic and dacrystic seizures. Surgery is the treatment of drug resistant hamartoma epilepsy, with associated positive results on endocrine, psychiatric and cognitive symptoms.Recently, alternatives to open microsurgical treatment have been proposed. We review these techniques and compare their efficacy and safety.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 73 publications
3
34
0
4
Order By: Relevance
“…A recent review article on HH surgery also suggested that multiple radiofrequency small lesions have better efficacy and safety than LITT, probably due to the difficulty of the latter technique in targeting the whole lesion while sparing the adjacent structure. 24 Nevertheless, this review also implied the necessity of taking into account the recent advances of LITT.…”
Section: Surgical Treatment Of Hhmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review article on HH surgery also suggested that multiple radiofrequency small lesions have better efficacy and safety than LITT, probably due to the difficulty of the latter technique in targeting the whole lesion while sparing the adjacent structure. 24 Nevertheless, this review also implied the necessity of taking into account the recent advances of LITT.…”
Section: Surgical Treatment Of Hhmentioning
confidence: 99%
“…5 To achieve this goal safely, clear demarcation between the HH and the hypothalamus is essential for creating an effective disconnection plane, as well as for avoiding additional damage to the hypothalamus. Because SRT has the disadvantage of not having a method of intraoperative monitoring for thermocoagulation area like MR thermometry in LITT, 24 accurate placement of the coagulation probe is crucial. Semimicrorecording showed the electrophysiological border between the hypothalamus and HH at the submillimeter level, which almost completely corresponded to the morphological border determined by MRI.…”
Section: Surgical Treatment Of Hhmentioning
confidence: 99%
“…40,41 Similarly, a cohort of children with generalized multiregional epileptic discharges on EEG associated with Lennox-Gastaut syndrome had good seizure outcomes and developmental quotient after resective surgery. 42 Children presenting with gelastic seizures due to HH have also had good outcomes from direct endoscopic removal, 43 radiation therapy, 44 and laser ablation. 45 Hence, the distinction between generalized and focal seizures as it pertains to surgical candidacy is less straightforward than previously recognized.…”
Section: Indicationsmentioning
confidence: 99%
“…Damit einhergehend, können hohe direkte, indirekt und intangible Kosten entstehen [5,6]. Zwar bietet eine epilepsiechirurgische Behandlung eine realistische Chance auf eine dauerhafte Anfallsfreiheit, birgt aufgrund der zentralen Lage des HH allerdings ein relevantes perioperatives Komplikationsrisiko, welches bei einer mikrochirurgischen Resektion zwischen 8 und 50 % liegt [7]. Zu den Komplikationen zählen Thalamusinfarkte, Gesichtsfelddefekte, endokrinologische Störungen und Gedächtnisprobleme [8].…”
unclassified